Large-scale carbon storage in the deep-sea through cold-water coral mounds off the Campeche Bank, Gulf of Mexico - L. Greiffenhagen; J. Titschack; C. Wienberg; L. H. De Clippele; L. Matos; J. Gafeira; A. Schröder-Ritzrau; K. Arul; N. Frank; D. Hebbeln (Coral Reefs, 2026)
Reef-building cold-water corals form large seabed structures known as coral mounds. As demonstrated in studies from the Northeast Atlantic and Mediterranean Sea, coral mounds accumulate large amounts of carbon(ate). However, beyond the scale of individual mounds, long-term accumulation of both organic (C org ) and inorganic carbon (C inorg ) at the mound province scale remains poorly quantified. In this study, we investigate the Campeche Mound Province, southern Gulf of Mexico, which consists of interconnected coral mound ridges covering an area of > 40 km 2 . Using sediment cores, we reconstruct total carbon (C org and C inorg ) accumulation in the Campeche Mounds over the past ~ 250 kyr. The results show mean total carbon accumulation rates of 0.5–5.6 g C cm −2 kyr −1 . This is three to nine times higher than on the surrounding seafloor. We then upscale obtained carbon concentration data to the entire mound province using high-resolution bathymetry and the CoMMa toolbox, a novel morphometric mapping tool. The total carbon storage of the Campeche Mounds amounts to an estimated 18.5 megatons of carbon that is transferred to the long-term carbon cycle and immobilised for millions of years. For the first time, we present a combination of core-based analysis and spatial mapping. Through accounting for different approaches and time scales, we provide reliable value ranges for carbon accumulation rates in coral mounds. The Campeche Mound Province is not fully mapped and likely much larger, highlighting the substantial, albeit overlooked long-term carbon burial through benthic deep-sea ecosystems in the southern Gulf of Mexico and beyond.

Time in the city: long-term urban exposure predicts greater exploration and problem solving in wild red foxes - F. Blake Morton; Dylan Thompson-Jones; Kristy A. Adaway; Koko M. Sutter; Catia Matos; Georgia B. Freer; Georgia A.A. Fletcher; Carl D. Soulsbury (Animal Behaviour, 2026)

The genus Pouteria: a review of advances in phytochemical elucidation and its pharmacological properties - Rafael C. Matos; Ana Flavia A. Bitencourt; Vanessa R. Prado; Alexsandro D. M. Oliveira; Renes R. Machado; Marina Scopel (Phytochemistry Reviews, 2026)
The genus Pouteria (family Sapotaceae) is traditionally used for gastrointestinal, inflammatory, and microbial issues, and has great nutritional applications because of the variety of fruits it contains. Despite its versatile applications, comprehensive research on Pouteria remains outdated, necessitating an integrative review of recent studies exploring its phytochemical evidence and biological activities. An unrestricted search in various databases (Jan/2009 to Aug/2022) focused on the genus “ Pouteria ”. Despite this genus having 325 recognized species, few studies have evaluated their bioactive potential, including antioxidant, anticancer, hypoglycemic, antimicrobial, anti-inflammatory, and antinociceptive, as well as their potential for treatment of Alzheimer disease. Regarding phytochemical evaluation, among the few substances isolated were a high number of terpenoids, flavonoids, phenolics, saponins, and others. In addition, owing to the high potential for fruit utilization, several primary metabolites were identified, which presented qualitative and quantitative diversity among species with the interests of the pharmaceutical industry. Therefore, this review provides information about phytochemical and pharmacological properties of the species of Pouteria . Given the shallow and incomplete results for several species, there is a demonstrated need for new studies encompassing all plant parts of Pouteria species, contributing to a more comprehensive understanding of their medicinal potential.

Multidrug-resistant Pseudomonas aeruginosa in ICU patients and hospital surfaces: β-lactamase burden, biofilm formation and clonal spread - Marcos Eduardo Passos da Silva; Luccas Manoel de Melo Suica; Renata Santos Rodrigues; Márlon Grégori Flôres Custódio; Valcimar Batista Ferreira; Leilane da Silva Pontes; Ivson Cassiano de Oliveira Santos; Bruno Rocha Pribul; Núcia Cristiane da Silva Lima; Izabelly Vitória Gotara Ramos; Anjo Gabriel Carvalho; Mayra Gyovana Leite Belém; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Native Trichoderma spp. as biocontrol agents against common beans anthracnose - S. C. Izidoro-Morimitsu; A. Knob; C. K. Matos; C. M. D. R. Faria; J. Kawakami (Journal of Plant Diseases and Protection, 2026)

Between campo rupestre and rainforest: evidence of conservative evergreen strategies in contrasting tropical environments - Rosineide Braz Santos Fonseca; Jamerson Souza da Costa; Leonardo Feijó Cadena de Oliveira Filho; Paulo Sérgio Santos-Neves; Adelly Cardoso de Araújo Fagundes; Alexsandro Bezerra-Silva; Maria Thereza Dantas Gomes; Álefy Gonçalves de Barros; Sinzinando Albuquerque-Lima; Vitor Alberto de Matos Pereira; Isiara Silva Menezes; Sâmia Paula Santos Neves; et al. (Journal of Mountain Science, 2026)

Bisphenol S and high-fat diet drive structural and inflammatory remodeling of the colon in C57Bl/6 male mice - Beatriz Gouvêa de Luca; Beatriz Alexandre-Santos; Kauet de Matos Gama e Souza; Emanuelle Barreto-Reis; Ana Paula de Paula Alves; Thaís de Souza Carvalho-Laureano; Vinicius Sepúlveda-Fragoso; Luiza Gil Diniz; Milena Barcza Stockler-Pinto; Clarice Machado dos Santos; Denise Pires de Carvalho; Leandro Miranda-Alves; et al. (Toxicology Letters, 2026)

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Land-use legacies drive distinct recovery trajectories and persistently shape the taxonomic and functional composition of tree communities - Vanessa de Souza Moreno; Fabio A.R. Matos; Ricardo G. César; Gabriel D. Colleta; Elisa Díaz García; Robin L. Chazdon; Pedro H.S. Brancalion (Forest Ecology and Management, 2026)

Rats, residues and rodenticide resistance: Hepatic concentration of anticoagulant rodenticides in genetically susceptible wild brown and black rats - Ana Carromeu-Santos; Beatriz Martín-Cruz; Tomé Neves; Elizandra Matos Cardoso; Naiara Guimarães Sales; Andrea Acosta Dacal; Ana Macías-Montes; Rita Pacheco; Bastiaan G. Meerburg; Allan D. McDevitt; Maria da Luz Mathias; Octavio Pérez Luzardo; et al. (Science of The Total Environment, 2026)

First record of Phyllorhiza punctata von Lendenfeld, 1884 (Cnidaria: Rhizostomeae) in Portuguese waters: implications for regional marine ecosystems - Antonina dos Santos; Alexandra D. Silva; Pedro F. Silva; Ana Matos; Elsa Froufe (Marine Biodiversity, 2026)

Chlorophyll- a dynamics in the lower Amazon River: insights from in situ and hyperspectral remote sensing using OCI-PACE - Aline de Matos Valerio; João L. Montanari; Milton Kampel; Nicholas D. Ward; Jeffrey E. Richey; Alan C. Cunha (International Journal of Remote Sensing, 2026)

Characterization and modeling approach for planning restoration strategies in a complex basin affected by acid mine drainage - Jonatan Romero-Matos; Laura Sánchez-López; Rafael León; Robert L. Runkel; D. Kirk Nordstrom; Carlos R. Cánovas; Francisco Macías; José Miguel Nieto (Journal of Environmental Management, 2026)

Mycobacterium bovis in the Dominican Republic, a study of detection, distribution and genomic variability - Raysa Elena Reyes Santiago; María Jimena Marfil; Juan de la Cruz Araujo Lara; Yorkiris Consuegra Martínez; René Espinal Lagares; Luis Matos Casado; María Esther D’oleo; Martín José Zumárraga; Soledad Barandiaran (Tropical Animal Health and Production, 2026)

Genetic correlations between carcass traits measured by ultrasonography and semen quality traits in Nellore cattle incorporating genomic information - Camila S. Mussi; Gabriel C. Medeiros; Rafael Espigolan; Fernando Baldi; Marcio R. Silva; José D. Guimarães; Elisangela C. Matos; Joanir P. Eler; Tamires Miranda Neto; José Bento S. Ferraz; Luiz F. Brito (Livestock Science, 2025)

The goat Longissimus thoracis et lumborum muscle proteome: effects of dry ageing and cooking in chevon - Menalda Valeriano André; Catarina Prista; Vítor D. Alves; David M. Ribeiro; Miguel Filipe Pedro; Laura Sacarrão-Birrento; Hugo Osório; André M. de Almeida; Teresa J.S. Matos (Food Research International, 2025)

Exposure to bisphenol S promotes renal damage via aryl hydrocarbon receptor and NF-κB pathways in a mice model of obesity - Michele Lima Brito; Joana Ramos de Araujo; Patricia Pereira Almeida; Beatriz Alexandre-Santos; Beatriz Gouvêa de Luca; Kauet de Matos Gama e Souza; Denise Pires de Carvalho; Denise Mafra; Eliete Dalla Corte Frantz; Clarice Machado-Santos; Leandro Miranda-Alves; D'Angelo Carlo Magliano; et al. (Environmental Research, 2025)

Here, There and Everywhere: Widespread Non‐Native Plants in the World's Urban Ecosystems - David M. Richardson; Lauren B. Trotta; Myla F. J. Aronson; Benjamin Baiser; Marc W. Cadotte; Marta Carboni; Laura Celesti‐Grapow; Sonja Knapp; Ingolf Kühn; Ana Carolina Lacerda de Matos; Zdeňka Lososová; Daijiang Li; et al. (Global Ecology and Biogeography, 2025)
Aim To (a) produce a list of the most widespread naturalised non‐native plant species across cities of the world; (b) explore whether cities on different continents are invaded by the same group of widespread naturalised species; and (c) elucidate the origins of the most widespread naturalised urban species. Location Global. Time Period No specific period. Major Taxa Studied Vascular plants. Method Using the most comprehensive and up‐to‐date dataset of non‐native urban floras yet assembled (GUBIC; Global Urban Biological Invasions Compendium), we identified the most widespread naturalised plant species (the global urban florome) by filtering for taxa present across all continents (except Antarctica) and their frequency in urban areas. To assess global patterns of urban plant naturalisation, we conducted ordination analyses and visualised species co‐occurrence. We also examined species origins and their environmental impact. Results Among the 7792 naturalised plant species recorded in 553 urban centres, 302 species (4%) were found on all six continents. Of these, 96 species, considered the most widespread species, were present in more than half of urban centres in Oceania, North America and South America; this proportion was higher than in Africa, Asia and Europe. Cities outside Europe and Asia are more homogeneous in terms of the species composition of the most widespread invaders. An analysis of species origins showed that temperate Asia contributed the most species globally, while intercontinental exchange patterns varied, with a notable one‐directional flow from North to South America. Main Conclusions Our results suggest that urban ecosystems outside Europe and Asia are more susceptible to recent invasions than those within these two continents. Understanding the composition and origins of these widespread species is crucial for developing coordinated management strategies and improving the resilience of urban biodiversity.

Addressing Critical Fungal Pathogens Under a One Health Perspective: Key Insights from the Portuguese Association of Medical Mycology - R. Sabino; F. Antunes; R. Araujo; A. R. Bezerra; J. Brandão; C. Carneiro; A. Carvalho; D. Carvalho; I. C. Conceição; F. Cota Medeiros; C. Cruz; E. Duarte; et al. (Mycopathologia, 2025)
Fungal infections have emerged as a significant public health concern, especially with the increasing incidence of severe mycoses caused by pathogens such as Aspergillus fumigatus , Candida auris , Candida albicans , and Cryptococcus neoformans . These fungi, listed as critical priorities by the World Health Organization, pose a heightened risk due to rising antifungal resistance and their severe impact on immunocompromised individuals. This article, coordinated by the Portuguese Association of Medical Mycology, highlights the importance of adopting a One Health perspective to address fungal threats comprehensively. Drawing on interdisciplinary collaboration, the association aims to foster greater awareness, improve diagnostic capabilities, and stimulate research and public health policies in Portugal but also at global level. The paper outlines key strategies for surveillance, prevention, and innovation in fungal diagnostics and therapeutics. Moreover, it emphasizes the urgent need for national coordination and international cooperation in managing fungal infections, advocating for integrative approaches that link human, animal, and environmental health. By presenting a consolidated overview of current challenges and future priorities, this work seeks to enhance preparedness and response mechanisms in the face of escalating fungal threats.

Combining protection and restoration strategies enables cost-effective compensation with ecological equivalence in Brazil - Clarice Borges-Matos; Francisco d'Albertas; Mariana Eiko Mendes; Rafael Loyola; Jean Paul Metzger (Environmental Impact Assessment Review, 2025)

Seagrass biochemical response to transplantation into contaminated sediments: A mesocosm experiment - Vitor H. Oliveira; B.A. Fonte; A.I. Sousa; B. Marques; D. Matos; B. Henriques; M.E. Pereira; C.B. Lopes; R. Calado; A.I. Lillebø; E. Figueira; J.P. Coelho (Environmental Research, 2025)

Enhancing commercial SOFCs fed directly with ethanol through a modified manganite coating - F. Matos de Oliveira; S. Vecino-Mantilla; Z. Hafsi; M.V. Barp; F. D’Acapito; A. Puri; J. Perez; E. Ticianelli; M. Lo Faro (Chemical Engineering Journal, 2025)

Corrigendum to “Synthesis of controlled size starch nanoparticles (SNPs) title of article” [Carbohydr. Polym. 250 (2020) 116938] - G. Gutiérrez; D. Morán; A. Marefati; J. Purhagen; M. Rayner; M. Matos (Carbohydrate Polymers, 2025)

Insights into the thermal stability properties of two hardwoods from the Amazon rainforest - L. de Souza-Cavalcante; F. Guerrero; J. Anglada-Rivera; Y. Leyet; F. M. A. da Silva; G. Q. Ramos; R. Matos; H. D. da Fonseca Filho (Journal of the Indian Academy of Wood Science, 2025)

The importance of tropical tree-ring chronologies for global change research - Peter Groenendijk; Flurin Babst; Valerie Trouet; Ze-Xin Fan; Daniela Granato-Souza; Giuliano Maselli Locosselli; Mulugeta Mokria; Shankar Panthi; Nathsuda Pumijumnong; Abrham Abiyu; Rodolfo Acuña-Soto; Eduardo Adenesky-Filho; et al. (Quaternary Science Reviews, 2025)

Metabolic response of Zostera noltei transplants in a historically contaminated ecosystem - V.H. Oliveira; D. Matos; A.I. Sousa; M. Dolbeth; B. Marques; A.I. Lillebø; M.E. Pereira; S. Díez; E. Figueira; J.P. Coelho (Journal of Environmental Management, 2025)

Enniatin B alters bovine polymorphonuclear leukocytes phagocytosis and extracellular reactive oxygen species production in vitro - S. Sandrini; G. Salvi; D. Ravanelli; V. Perricone; L.G. De Matos; F. Ceciliani; C. Lecchi; A. Agazzi (Research in Veterinary Science, 2025)

Transplantation of seagrass (Zostera noltei) as a potential nature-based solution for the restoration of historically contaminated mudflats - Vítor H. Oliveira; B.A. Fonte; A.I. Sousa; D. Crespo; J.M. Dias; N. Vaz; D. Matos; E. Figueira; M.E. Pereira; A.I. Lillebø; M. Dolbeth; J.P. Coelho (Science of The Total Environment, 2025)

Investigating multiple vegetable oils and recycled variant for microplastics extraction from water, integrated with Raman spectroscopy - R. Garzón-Vidueira; D. Rede; R. Rial-Otero; R. Vilarinho; J.A. Moreira; S. Jorge; M. André; R. Barbosa; C. Delerue-Matos; V. Cruz Fernandes (Science of The Total Environment, 2024)

Human and Hurricane Impacts to Mangroves Modulate Overwash Deposition to a Back-Barrier Lagoon - Frances Griswold; Pedro I. Matos-Llavona; Jonathan D. Woodruff; Brian C. Yellen (Estuaries and Coasts, 2024)

Disentangling the veil line for Brazilian biodiversity: An overview from two long-term research programs reveals huge gaps in ecological data reporting - Aretha Franklin Guimaraes; Luciano Carramaschi de Alagao Querido; Taina Rocha; Domingos de Jesus Rodrigues; Pedro Lage Viana; Helena de Godoy Bergallo; Geraldo Wilson Fernandes; Tiago Shizen Pacheco Toma; Helena Streit; Gerhard Ernst Overbeck; Alberico Queiroz Salgueiro de Souza; Albertina Pimentel Lima; et al. (Science of The Total Environment, 2024)

Disseminated paracoccidioidomycosis in a captive western black-handed tamarin (Saguinus niger) - Isabelle D. de Oliveira; Eduardo Ferreira-Machado; Jamile M. Garcia; Sarah R.J.S. Simões; Ketlyn B. Figueiredo; Rodrigo A. Ressio; André L.M. da Costa; Flora N. Matos; Cássia R.R. Gonzaga; Shamira S. Leandro; Marina A. de Medeiros; Rodrigo H.F. Teixeira; et al. (Journal of Comparative Pathology, 2024)

SARS-CoV2 Nsp1 is a metal-dependent DNA and RNA endonuclease - Bruno A. Salgueiro; Margarida Saramago; Mark D. Tully; Federico Issoglio; Sara T. N. Silva; Ana C. F. Paiva; Cecília M. Arraiano; Pedro M. Matias; Rute G. Matos; Elin Moe; Célia V. Romão (BioMetals, 2024)
Over recent years, we have been living under a pandemic, caused by the rapid spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV2). One of the major virulence factors of Coronaviruses is the Non-structural protein 1 (Nsp1), known to suppress the host cells protein translation machinery, allowing the virus to produce its own proteins, propagate and invade new cells. To unveil the molecular mechanisms of SARS-CoV2 Nsp1, we have addressed its biochemical and biophysical properties in the presence of calcium, magnesium and manganese. Our findings indicate that the protein in solution is a monomer and binds to both manganese and calcium, with high affinity. Surprisingly, our results show that SARS-CoV2 Nsp1 alone displays metal-dependent endonucleolytic activity towards both RNA and DNA, regardless of the presence of host ribosome. These results show Nsp1 as new nuclease within the coronavirus family. Furthermore, the Nsp1 double variant R124A/K125A presents no nuclease activity for RNA, although it retains activity for DNA, suggesting distinct binding sites for DNA and RNA. Thus, we present for the first time, evidence that the activities of Nsp1 are modulated by the presence of different metals, which are proposed to play an important role during viral infection. This research contributes significantly to our understanding of the mechanisms of action of Coronaviruses.

P15-15 Unveiling the therapeutic potential of MSC-derived conditioned media and exosomes towards COVID-19-induced neurological sequelae - C.M. Trigo; S.P. Camões; A.S. Serras; A.T. Matos; R. Vitorino; A.R. Vaz; D. Brites; S. Solá; J.P. Miranda (Toxicology Letters, 2024)

Fisheries and the COVID-19 pandemic: A global scoping review of the early pressures, impacts, and responses in least developed, emerging, and developed countries - Richard A. Nyiawung; Taylor Ehrlick; Nathan J. Bennett; Nicolas D. Brunet; Fabio Matos; Cristina Pita; Joshua S. Stoll; Philip A. Loring (Regional Studies in Marine Science, 2024)

Invasive non-native species in Brazil: an updated overview - Rafael D. Zenni; Sílvia R. Ziller; Clarissa A. da Rosa; Rafael B. Sühs; Patricia B. Puechagut; Beloni T. P. Marterer; Gustavo Heringer; Ana Carolina L. de Matos; Marina L. Bueno; Jonathan W. Almeida; Carlos H. T. Silva; José Renato Legracie-Júnior; et al. (Biological Invasions, 2024)

Antimicrobial resistance patterns of Staphylococcus spp. isolated from clinical specimens of companion animals in Northern Portugal, 2021–2023 - D. Araújo; R. Oliveira; B.L. Silva; J. Castro; C. Ramos; F. Matos; C. Almeida; S. Silva (The Veterinary Journal, 2024)

The decline and death of Canary Island date palms in México City is associated with subgroup 16SrIV-D phytoplasmas - C. F. Ortiz-García; D. Alvarado-Rosales; C. Oropeza; L. de L. Saavedra-Romero; S. Aranda-Ocampo; A. Almaraz-Sánchez; A. Quezada-Salinas; A. Equihua-Martínez; S. E. García-Díaz; M. Narváez; G. Nic-Matos; P. J. Palma-Cancino; et al. (Australasian Plant Pathology, 2024)

Melatonin acts through different mechanisms to control oxidative stress and primordial follicle activation and survival during in vitro culture of bovine ovarian tissue - Bianca R. Silva; Francisco C. Costa; Miguel F. De Lima Neto; Francisco F. Caetano Filho; Ernando I.T. de Assis; Francisco L.N. Aguiar; Anderson W.B. Silva; Solano D. Martins; Valdevane R. Araújo; Maria H.T. Matos; José J.N. Costa; José R.V. Silva (Domestic Animal Endocrinology, 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

Supporting Nature-Based Solutions via Nature-Based Thinking across European and Latin American cities - Geovana Mercado; Tom Wild; Jaime Hernandez-Garcia; Mariana D. Baptista; Martina van Lierop; Olivia Bina; Andy Inch; Åsa Ode Sang; Arjen Buijs; Cynnamon Dobbs; Alexis Vásquez; Alexander van der Jagt; et al. (Ambio, 2024)
Nature-Based Solutions concepts and practices are being used worldwide as part of attempts to address societal challenges but have also been criticised for not dealing with deeper transformations needed to face urgent issues including biodiversity loss, climate change and inclusion. In this paper, we explore how an inclusive, integrated and long-sighted approach, emphasising a more radical integration of nature within cities, might support the transformations needed to endure major contemporary challenges. Addressing important emerging critiques of Nature-Based Solutions, we consider the potential of a more incisive form of Nature-Based Thinking (NBT) in cities, based on more holistic perspectives. The paper draws on a reflective and iterative research process that engaged both the research and practice communities through a symposium and a series of futures workshops that together explored the potential of NBT to develop future nature-cities relations in Europe and Latin America. The results of the reflective process suggest that notions of nature with people —not for people— new organisational structures, and the intention and capacity to apply long-term perspectives, are needed when planning for NBS interventions aimed at sustainable urban development. This includes developing a cultural-structural change based on new and inclusive understandings of human–nature relations, and novel governance paradigms that allow cross-sectoral coordination and engagement of local stakeholders beyond formal organisational structures.

Trends in valuation approaches for cultural ecosystem services: A systematic literature review - Laura Andreina Matos Márquez; Eva Caroline Nunes Rezende; Karine Borges Machado; Emilly Layne Martins do Nascimento; Joana D'arc Bardella Castro; João Carlos Nabout (Ecosystem Services, 2023)

Contrasting levels of β‐diversity and underlying phylogenetic trends indicate different paths to chemical diversity in highland and lowland willow species - Martin Volf; Jing Vir Leong; Paola de Lima Ferreira; Tereza Volfová; Petr Kozel; Pável Matos‐Maraví; Elvira Hörandl; Natascha D. Wagner; Niko Luntamo; Juha‐Pekka Salminen; Simon T. Segar; Brian E. Sedio (Ecology Letters, 2023)
Diverse specialised metabolites contributed to the success of vascular plants in colonising most terrestrial habitats. Understanding how distinct aspects of chemical diversity arise through heterogeneous environmental pressures can help us understand the effects of abiotic and biotic stress on plant evolution and community assembly. We examined highland and lowland willow species within a phylogenetic framework to test for trends in their chemical α‐diversity (richness) and β‐diversity (variation among species sympatric in elevation). We show that differences in chemistry among willows growing at different elevations occur mainly through shifts in chemical β‐diversity and due to convergence or divergence among species sharing their elevation level. We also detect contrasting phylogenetic trends in concentration and α‐diversity of metabolites in highland and lowland willow species. The resulting elevational patterns contribute to the chemical diversity of willows and suggest that variable selective pressure across ecological gradients may, more generally, underpin complex changes in plant chemistry.

Exploring the prevalence and antibiotic resistance profile of Klebsiella pneumoniae and Klebsiella oxytoca isolated from clinically ill companion animals from North of Portugal - D. Araújo; J. Castro; F. Matos; R. Oliveira; C. Ramos; C. Almeida; S. Silva (Research in Veterinary Science, 2023)

Effects of dredging activities and seasonal variation on coastal plankton assemblages: results from 10 years of environmental monitoring - Lohengrin D. A. Fernandes; Guilherme N. Corte; Laura Moura; Carolina Reis; Thiago Matos; Danubia Moreno; Pedro Sant’ Anna Cortez; Wanderson Fernandes de Carvalho; Wanda Monteiro-Ribas; José Eduardo A. Gonçalves; Fernando Ribeiro; Fernanda Thomazelli; et al. (Environmental Monitoring and Assessment, 2023)

A bioinformatic platform to integrate target capture and whole genome sequences of various read depths for phylogenomics - Pedro G. Ribeiro; María Fernanda Torres Jiménez; Tobias Andermann; Alexandre Antonelli; Christine D. Bacon; Pável Matos‐Maraví (Molecular Ecology, 2021)
The increasing availability of short‐read whole genome sequencing (WGS) provides unprecedented opportunities to study ecological and evolutionary processes. Although loci of interest can be extracted from WGS data and combined with target sequence data, this requires suitable bioinformatic workflows. Here, we test different assembly and locus extraction strategies and implement them into secapr , a pipeline that processes short‐read data into multilocus alignments for phylogenetics and molecular ecology analyses. We integrate the processing of data from low‐coverage WGS ( k mer simultaneously for assembly results in the highest yield of extracted loci from de novo assembled contigs, while data sets derived from sequencing read depths as low as 5× recovers the expected species relationships in phylogenetic trees. By making the tested assembly approaches available in the secapr pipeline, we hope to inspire future studies to incorporate complementary data and make an informed choice on the optimal assembly strategy.

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Evaluation of chelating and cytoprotective activity of vanillin against the toxic action of mercuric chloride as an alternative for phytoremediation - Joelma P. da Silva; Maria do S. Costa; Fabia F. Campina; Camila F. Bezerra; Thiago S. de Freitas; Amanda K. Sousa; Celestina E. Sobral Souza; Yedda M. L. S. de Matos; Francisco N. Pereira-Junior; Irwim R. A. Menezes; Henrique D. M. Coutinho; Janaína E. Rocha (Environmental Geochemistry and Health, 2021)

Stereometric analysis of Amazon rainforest Anacardium occidentale L. leaves - Glenda Q. Ramos; Ítalo C. da Costa; Marcelo E. H. Maia da Costa; Erveton P. Pinto; Robert S. Matos; Henrique D. da Fonseca Filho (Planta, 2021)

Salinity Biases and the Variability of the Atlantic Meridional Overturning Circulation in GFDL-CM3 - Fernanda D. A. O. Matos; Janini Pereira; Marcus Dengler (Ocean Science Journal, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Pilot-Scaled Fast-Pyrolysis Conversion of Eucalyptus Wood Fines into Products: Discussion Toward Possible Applications in Biofuels, Materials, and Precursors - Mailson Matos; Bruno D. Mattos; Pedro H. G. de Cademartori; Tainise V. Lourençon; Fabrício A. Hansel; Patrícia R. S. Zanoni; Carlos I. Yamamoto; Washington L. E. Magalhães (BioEnergy Research, 2020)

Histopathology associated with infection by Procamallanus (Spirocamallanus) inopinatus (Nematoda) in farmed Brycon cephalus (Characiformes) from Peru: a potential fish health problem - Norma L. S. Rivadeneyra; Omar Mertins; Ruben C. Cuadros; Jose C. O. Malta; Lorena V. de Matos; Patrick D. Mathews (Aquaculture International, 2020)

Chitosan for direct bioflocculation of wastewater - Eric Lichtfouse; Nadia Morin-Crini; Marc Fourmentin; Hassiba Zemmouri; Inara Oliveira do Carmo Nascimento; Luciano Matos Queiroz; Mohd Yuhyi Mohd Tadza; Lorenzo A. Picos-Corrales; Haiyan Pei; Lee D. Wilson; Grégorio Crini (Environmental Chemistry Letters, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Purinergic system as a potential target for inflammation and toxicity induced by thymol in immune cells and tissues - Matheus D. Baldissera; Carine F. Souza; Antônio Francisco Igor M. De Matos; Bernardo Baldisserotto; Lenita M. Stefani; Aleksandro S. da Silva (Molecular and Cellular Biochemistry, 2019)

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

In Silico, In Vitro and In Vivo Toxicological Assessment of BPP-BrachyNH2, A Vasoactive Proline-Rich Oligopeptide from Brachycephalus ephippium - Daniel D. R. Arcanjo; Ana Carolina Mafud; Andreanne G. Vasconcelos; José Couras da Silva-Filho; Maurício P. M. Amaral; Lucas M. Brito; Marcelo P. Bemquerer; Selma A. S. Kückelhaus; Alexandra Plácido; Cristina Delerue-Matos; Nuno Vale; Yvonne P. Mascarenhas; et al. (International Journal of Peptide Research and Therapeutics, 2017)

The role of the P2X7 receptor in murine cutaneous leishmaniasis: aspects of inflammation and parasite control - Vanessa Ribeiro Figliuolo; Suzana Passos Chaves; Luiz Eduardo Baggio Savio; Maria Luiza Prates Thorstenberg; Érika Machado Salles; Christina Maeda Takiya; Maria Regina D’Império-Lima; Herbert Leonel de Matos Guedes; Bartira Rossi-Bergmann; Robson Coutinho-Silva (Purinergic Signalling, 2017)

Evaluation of Primary Production in the Lower Amazon River Based on a Dissolved Oxygen Stable Isotopic Mass Balance - William C. Gagne-Maynard; Nicholas D. Ward; Richard G. Keil; Henrique O. Sawakuchi; Alan C. Da Cunha; Vania Neu; Daimio C. Brito; Diani F. Da Silva Less; Joel E. M. Diniz; Aline De Matos Valerio; Milton Kampel; Alex V. Krusche; et al. (Frontiers in Marine Science, 2017)

Peripheral and central antinociceptive effects of the butanolic fraction of Byrsonima verbascifolia leaves on nociception-induced models in mice - A. A. Saldanha; J. M. Siqueira; A. H. F. Castro; N. A. Matos; A. Klein; D. B. Silva; C. A. Carollo; A. C. Soares (Inflammopharmacology, 2017)

Simulation of Subsurface Multiphase Contaminant Extraction Using a Bioslurping Well Model - Michelle Matos de Souza; Mart Oostrom; Mark D. White; Gerson Cardoso da Silva; Maria Claudia Barbosa (Transport in Porous Media, 2016)

A phylogeny of Lophocoleaceae-Plagiochilaceae-Brevianthaceae and a revised classification of Plagiochilaceae - Simon D. F. Patzak; Matt A. M. Renner; Alfons Schäfer-Verwimp; Kathrin Feldberg; Margaret M. Heslewood; Denilson F. Peralta; Aline Matos de Souza; Harald Schneider; Jochen Heinrichs (Organisms Diversity & Evolution, 2016)

Cometabolic Degradation of Anti-Inflammatory and Analgesic Pharmaceuticals by a Pentane Enrichment Culture - I. Bragança; A. S. Danko; J. Pacheco; D. Frascari; C. Delerue-Matos; V. F. Domingues (Water, Air, & Soil Pollution, 2016)

Oral and endotracheal tubes colonization by periodontal bacteria: a case–control ICU study - A. N. Porto; S. C. Cortelli; A. H. Borges; F. Z. Matos; D. R. Aquino; T. B. Miranda; F. Oliveira Costa; A. F. Aranha; J. R. Cortelli (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Genetic diversity of porcine sapoviruses in pigs from the Amazon region of Brazil - Juliana das Merces Hernandez; Daniel Camargo Stangarlin; Jones Anderson Monteiro Siqueira; Darleise de Souza Oliveira; Thayara Morais Portal; Aline Fernandes Barry; Fabrício Aleixo Dias; Jane Cecilia Silveira de Matos; Joana D’Arc Pereira Mascarenhas; Yvone Benchimol Gabbay (Archives of Virology, 2013)

Geology of the Rosário–Neves Corvo antiform, Iberian Pyrite Belt, Portugal: new insights from physical volcanology, palynostratigraphy and isotope geochronology studies - J. T. Oliveira; C. J. P. Rosa; Z. Pereira; D. R. N. Rosa; J. X. Matos; C. M. C. Inverno; T. Andersen (Mineralium Deposita, 2013)

PAH air pollution at a Portuguese urban area: carcinogenic risks and sources identification - K. Slezakova; J. C. M. Pires; D. Castro; M. C. M. Alvim-Ferraz; C. Delerue-Matos; S. Morais; M. C. Pereira (Environmental Science and Pollution Research, 2013)

Chloroplast SSR genetic diversity indicates a refuge for Corylus avellana in northern Portugal - S. Martins; F. Simões; D. Mendonça; J. Matos; A. P. Silva; V. Carnide (Genetic Resources and Crop Evolution, 2013)

Strong site fidelity and longer internesting interval for solitary nesting olive ridley sea turtles in Brazil - Lélia Matos; Augusto C. C. D. Silva; Jaqueline C. Castilhos; Marilda I. Weber; Luciano S. Soares; Luís Vicente (Marine Biology, 2012)

Diet and the risk of head and neck cancer: a pooled analysis in the INHANCE consortium - Shu-Chun Chuang; Mazda Jenab; Julia E. Heck; Cristina Bosetti; Renato Talamini; Keitaro Matsuo; Xavier Castellsague; Silvia Franceschi; Rolando Herrero; Deborah M. Winn; Carlo La Vecchia; Hal Morgenstern; et al. (Cancer Causes & Control, 2012)

Evaluation of respiratory chain activity in lymphocytes of patients with Alzheimer disease - Pollyana Feldhaus; Daiane B. Fraga; Fernando V. Ghedim; Renata D. De Luca; Thiago D. Bruna; Matheus Heluany; Maria Paula Matos; Gabriela K. Ferreira; Isabela C. Jeremias; Claudia Heluany; Emilio L. Streck; Alexandra I. Zugno (Metabolic Brain Disease, 2011)

Behavioral changes and mitochondrial dysfunction in a rat model of schizophrenia induced by ketamine - Larissa de Oliveira; Daiane B. Fraga; Renata D. De Luca; Leila Canever; Fernando V. Ghedim; Maria Paula P. Matos; Emilio L. Streck; João Quevedo; Alexandra I. Zugno (Metabolic Brain Disease, 2011)

sTNFR-1 is an early inflammatory marker in community versus institutionalized elderly women - Fernanda Matos Coelho; F. M. S. Narciso; D. M. G. Oliveira; D. S. Pereira; A. L. Teixeira; M. M. Teixeira; D. G. Souza; L. S. M. Pereira (Inflammation Research, 2010)

Bulk adhesive strength of recombinant hybrid mussel adhesive protein - Hyung Joon Cha; Dong Soo Hwang; Seonghye Lim; James D. White; Cristina R. Matos-Perez; Jonathan J. Wilker (Biofouling, 2009)

Cholesterol depletion by methyl-?-cyclodextrin enhances myoblast fusion and induces the formation of myotubes with disorganized nuclei - Cludia S. Mermelstein; Dbora M. Portilho; Rommel B. Medeiros; Aline R. Matos; Marcelo Einicker-Lamas; Giovane G. Tortelote; Adalberto Vieyra; Manoel L. Costa (Cell and Tissue Research, 2005)

Antigenic and genetic diversity of early European isolates of Infectious bursal disease virus prior to the emergence of the very virulent viruses: early European epidemiology of Infectious bursal disease virus revisited? - K. Domanska; T. Mato; G. Rivallan; K. Smietanka; Z. Minta; C. de Boisseson; D. Toquin; B. Lomniczi; V. Palya; N. Eterradossi (Archives of Virology, 2004)

Fire and restoration of the largest urban forest of the world in Rio de Janeiro City, Brazil - D.M. Silva Matos; C. Junius F. Santos; D. de R. Chevalier (Urban Ecosystems, 2002)

Effects of pH and Dose on Nasal Absorption of Scopolamine Hydrobromide in Human Subjects - Shamim Ahmed; Anthony P. Sileno; Jorge C. deMeireles; Ramneik Dua; Harish K. Pimplaskar; Wei J. Xia; John Marinaro; Edward Langenback; Frank J. Matos; Lakshmi Putcha; Vincent D. Romeo; Charan R. Behl (Pharmaceutical Research, 2000)